Strategi Implementasi Kolaboratif untuk Menjawab Tantangan Ketenagakerjaan di Era Transformasi: Analisis Peran Negara, Dunia Usaha, dan Serikat Pekerja - Imron Natsir (Global Leadership Organizational Research in Management, 2025)
This study examines collaborative implementation strategies as an effective model for addressing employment challenges in the era of economic and technological transformation. Focusing on collaboration among the state, business sector, and labor unions, the study adopts a qualitative-descriptive approach through literature review, policy analysis, and case studies. Findings reveal that trilateral partnerships—inspired by the European concept of flexicurity—promote enhanced job security, worker productivity, and adaptability. The empowerment of labor unions through collective agreements and mediation has proven to strengthen industrial dialogue and prevent conflict. In Australia’s public sector, consultative committees involving union delegates and management demonstrate the effectiveness of consensus-based policymaking. Strategic recommendations include strengthening dialogic capacities, process digitalization, and the application of worker-driven social responsibility (WDSR) models for platform-based employment. The study concludes that multistakeholder collaborative networks are key to reinforcing labor market resilience and advancing social justice.